Experimental determination of interfacial energies for solid Sn in equilibrium with Sn-Mg-Zn liquid - Altintas, Yemliha; Ozturk, Esra; Aksoz, Sezen; Keslioglu, Kazim; Marasli, Necmettin (KOREAN INST METALS MATERIALS, 2015)
The equilibrated grain boundary groove shapes of solid Sn in equilibrium with Sn-Mg-Zn liquid were observed from a quenched sample by using a radial heat flow apparatus. The Gibbs-Thomson coefficient, solid-liquid interfacial energy and grain boundary energy of solid Sn were determined from the observed grain boundary groove shapes. The thermal conductivity of the eutectic solid phase for Sn-8.12 at% Mg-4.97 at% Zn alloy and the thermal conductivity ratio of the liquid phase to the solid phase for Sn-8.12 at% Mg-4.97 at% Zn alloy at eutectic temperature were also measured with a radial heat flow apparatus and a Bridgman-type growth apparatus, respectively. The Gibbs-Thomson coefficient, solid-liquid interfacial energy and grain boundary energy of solid Sn in equilibrium with Sn-Mg-Zn liquid were determined to be (8.3 +/- 0.6)x10(-8) Km, (118.5 +/- 14.2)x10(-3) Jm(-2) and (225.1 +/- 29.3)x10(-3) J m(-2) respectively from observed grain boundary groove shapes. A comparison of present results for solid Sn in the Sn-8.12 at% Mg-4.97 at% Zn alloy with the results obtained in previous works for similar solid Sn in equilibrium with different binary or ternary liquid was made.
Keywords: alloys; solidification; interfaces; thernal conductivity; thermal analysis; THERMAL-CONDUCTIVITY; SURFACE ENERGIES; AL-CU; METALS; MELT; ICE; CD; Materials Science; Metallurgy & Metallurgical Engineering